2011
DOI: 10.3109/0886022x.2011.605529
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy Associated with Peritonitis in Peritoneal Dialysis Patient

Abstract: Takotsubo cardiomyopathy (TTC) is characterized by clinical and electrocardiographic features that mimic acute myocardial infarction, normal or mildly elevated cardiac enzymes, distinctive left ventricular wall motion abnormalities, and absence of significant obstructive coronary artery disease. Often there is a history of emotional stress and usually encountered in postmenopausal women. Excessive catecholamine stimulation plays an important role in the pathogenesis of TTC. Usually, this condition is reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Some patients even present with normal concentrations of the corresponding necrosis biomarkers of the myocardium, despite severe symptoms or transient wall motion defects in the ventriculography or echocardiography mimicking myocardial ischemia. 11,21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients even present with normal concentrations of the corresponding necrosis biomarkers of the myocardium, despite severe symptoms or transient wall motion defects in the ventriculography or echocardiography mimicking myocardial ischemia. 11,21…”
Section: Resultsmentioning
confidence: 99%
“…Some patients even present with normal concentrations of the corresponding necrosis biomarkers of the myocardium, despite severe symptoms or transient wall motion defects in the ventriculography or echocardiography mimicking myocardial ischemia. 11,21 From our review, we observed that cardiac enzymes were provided in 73% of the cases. Among these cases, the TnI enzyme was elevated in 10 patients, CKMB in 9 patients, and TnT and CK in 5 and 3 patients, respectively (see Table 3 for descriptive statistics).…”
Section: Cardiac and Hemodynamic Biomarkersmentioning
confidence: 89%
“…Of a total of 1725 articles found [1341 with the precise Medical Subject Headings term (TTC)], we selected 26 articles dealing with 27 case reports (Table 1), 12 37 with an expected higher prevalence of women (n = 20, 74.1%). The mean age was 61.4 ± 13.7 years and bacterial infections were more frequent (n = 23, 85.2%).…”
Section: Resultsmentioning
confidence: 99%
“…There are few descriptions of the Takotsubo syndrome in patients with ESRD [2][3][4][5][6]. In each of these cases, a physical or emotional stress preceded the onset.…”
Section: Fig 2 -Magnetic Resonance Imaging (Mri) T2-map Sequences; Panel a 4-chamber End-diastolic (Panel A1) And End-systolic Images (Pamentioning
confidence: 99%